PENGEMBANGAN NILAI-NILAI KESENIAN CAN MACANAN KADDHUK UNTUK MENINGKATKAN KEPUASAN KARIER BAGI MAHASANTRI PONDOK PESANTREN IBNU KATSIR 1 JEMBER - Hayin, Dimas Samsul Ma'arif; Mudafiatun Isriyah; Wahid Suharmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to Develop the Artistic Values of Can Macanan Kaddhuk to Increase Career Satisfaction for students of the Ibnu Katsir 1 Islamic Boarding School Jember. Through the art of Can Macanan Kaddhuk, students are introduced to the concept of local values that contain messages of wisdom, such as the importance of maintaining harmony, respecting nature, and maintaining social relationshipsThis module is designed with a research and development (R&D) method that involves several stages, ranging from needs analysis, design, expert validation, to limited trials. The results of the study show that this module is effective in developing the Arts Values of Can Macanan Kaddhuk in Increasing Career Satisfaction for Students. Mahasantri who take part in this module experience positive changes in their behavior, and attitudes. Thus, this module is expected to be one of the solutions to help students at PPA Ibnu Katsir 1 Jember in Increasing Career Satisfaction For the students of the Ibnu Katsir Islamic Boarding School 1 Jember